Transfusion-Transmitted Cache Valley Virus Infection in a Kidney Transplant Recipient With Meningoencephalitis. (27th July 2022) - Al-Heeti, Omar; Wu, En-Ling; Ison, Michael G; Saluja, Rasleen K; Ramsey, Glenn; Matkovic, Eduard; Ha, Kevin; Hall, Scott; Banach, Bridget; Wilson, Michael R; Miller, Steve; Chiu, Charles Y; et al.
Abstract: Background: Cache Valley virus (CVV) is a mosquito-borne virus that is a rare cause of disease in humans. In the fall of 2020, a patient developed encephalitis 6 weeks following kidney transplantation and receipt of multiple blood transfusions. Methods: After ruling out more common etiologies, metagenomic next-generation sequencing (mNGS) of cerebrospinal fluid (CSF) was performed. We reviewed the medical histories of the index kidney recipient, organ donor, and recipients of other organs from the same donor and conducted a blood traceback investigation to evaluate blood transfusion as a possible source of infection in the kidney recipient. We tested patient specimens using reverse-transcription polymerase chain reaction (RT-PCR), the plaque reduction neutralization test, cell culture, and whole-genome sequencing. Results: CVV was detected in CSF from the index patient by mNGS, and this result was confirmed by RT-PCR, viral culture, and additional whole-genome sequencing. The organ donor and other organ recipients had no evidence of infection with CVV by molecular or serologic testing. Neutralizing antibodies against CVV were detected in serum from a donor of red blood cells received by the index patient immediately prior to transplant. CVV neutralizing antibodies were also detected in serum from a patient who received the co-component plasma from the same blood donation. Conclusions: Our investigation demonstrates probable CVV transmission through blood transfusion. Clinicians should consider arboviral infections in unexplained meningoencephalitis after blood transfusion or organ transplantation. The use of mNGS might facilitate detection of rare, unexpected infections, particularly in immunocompromised patients. Abstract : We present a case of Cache Valley virus meningoencephalitis in a kidney transplant patient who likely acquired the infection through blood transfusion. Use of metagenomic next-generation sequencing can facilitate the preliminary diagnosis in complicated cases, particularly in immunocompromised hosts.